Spatial Extensions of Excited States of Metal Complexes. Tunability by Chemical Variation - Yersin, Hartmut; Humbs, Werner (Inorganic chemistry, 1999)
The ligand−ligand coupling in excited states of homoleptic metal−organic and related compounds of the platinum metal group depends strongly on the metal d or MLCT character in these states. In particular, in triplet states, which mostly represent the lowest excited states, the metal participation is displayed in the amount of zero-field splitting (zfs). Detailed investigations in recent years have demonstrated that complexes with very small metal participation and thus small zfs, like [Rh(bpy)3]3+ and [Pt(bpy)2]2+, exhibit spatially localized or ligand-centered triplets. Compounds with large metal character as in 3MLCT states have large zfs, and the states are delocalized over the metal and the different ligands, as found for [Ru(bpy)3]2+ and [Os(bpy)3]2+. By chemical variation, it is possible to obtain a compound characterized by an intermediate position between the two extreme situations. Such a compound is Pt(2-thpy)2 with 2-thpy- = 2-(2-thienylpyridinate). It is one of the main subjects of this investigation to study whether in Pt(2-thpy)2 the lowest excited triplet is spatially extended over both ligands. This is done by comparing highly resolved emission (and excitation) spectra of perprotonated Pt(2-thpy-h 6)2, partially deuterated Pt(2-thpy-h 6)(2-thpy-d 6), and perdeuterated Pt(2-thpy-d 6)2. These spectra display clear fingerprints with respect to spatial extensions of the excited states. The required high resolution is obtained when the compounds are dissolved in an n-octane matrix (Shpol'skii matrix) and are measured at low temperature (T = 1.3 and 4.2 K). The deuterated compounds are studied for the first time. Interestingly, it is found that all three triplet sublevels of Pt(2-thpy)2 are spatially extended over both ligands. This result is of high importance, since it tells us that already a moderate metal d or MLCT character in the lowest triplet state of homoleptic compounds of the platinum metal group leads, at least in a rigid matrix, to spatially delocalized excited states.